RELIGIOUS MODERATION CYBER: SEBUAH STRATEGI PENGARUSUTAMAAN MELALUI LITERASI MEDIA BARU - Sauqi Futaqi; Saepudin Mashuri (Tatar Pasundan: Jurnal Diklat Keagamaan, 2021)
This study aims to examine mainstreaming strategies through new media in the cyber world as an effort to find alternative formulation on enriching religious moderation’s life. The methodology used in this study is qualitative through intertextuality techniques. The findings show the results of data collected. All those three stages have emerged religious moderation cyber. As a result, it turns out that media provides convenience for religious people in accessing information and establishing relationships, but on the other hand the media is also often used as a channel to spread radical understanding, hoaxes, and spread hatred.        Keywords: Religious Moderation; Mainstreaming Strategy; New Media Literacy